The expendables 2 [videorecording (DVD)] - West, Simon, 1961-; Stallone, Sylvester; Stallone, Sylvester; Statham, Jason, 1967-; Li, Jet, 1963-; Lundgren, Dolph, 1959-; Norris, Chuck, 1940-; Crews, Terry, 1968-; Hemsworth, Liam, 1990-; Damme, Jean-Claude van, 1960-; Willis, Bruce, 1955-; Schwarzenegger, Arnold (Lions Gate Films, 2012)
When Mr. Church decides to reunite the Expendables, and one of their men is murdered on the job, their quest for revenge puts them deep in enemy territory and up against an unexpected threat.